Provoke : how leaders shape the future by overcoming fatal human flaws - Tuff, Geoff, 1970-; Goldbach, Steve, 1973- (John Wiley & Sons, Inc., 2021)
"The world is becoming harder and harder to predict. But inevitably some uncertainties will resolve to being certain, with only the timing and impact remaining unclear. It is in this ?phase change? that people struggle most. Human beings are naturally wired to take a ?wait and see? approach to managing uncertainty. But it is the opposite reaction that will actually help business leaders win in the remade world. Provoke frames why we act the way we do when faced with uncertainty and provides tools to do things differently. Rooted at the intersection between business and behavioral economics, the book explores the topic as it relates to other aspects of the human experience as well ? teaching people across all walks of life how to provoke action as a mechanism to advance."--